The Relationship between the Use of Social Media as an English Learning Media and Students' Learning Motivation of the Eleventh Graders - Khatami Abror; Heru Setiawan (Didascein : Journal of English Education, 2024)
This research explores the impact of social media on learning motivation among eleventh-grade students at SMA PUSRI Palembang. The data was taken by involving 84 students as samples. The data was using a Social Media Questionnaire and Students’ Learning Motivation. By comparing the characteristics of social media questionnaire responses and students' learning motivation, the study aimed to determine the relationship between social media usage and learning motivation. Correlation analysis revealed a robust positive association between students' learning motivation and their use of social media for English learning. The correlation coefficient (r-value) of 0.925 exceeded the critical threshold (r_table) of 0.212, signifying statistical significance. It indicates a substantial link between social media as an English learning tool (X) and students' learning motivation (Y). Furthermore, the regression analysis demonstrated the significant impact of social media on students' motivation to learn. The significance level (alpha) was less than 0.05, and the t-value of 22.016 exceeded the required t-table value of 1.663. In summary, social media has significantly enhanced students' motivation to learn English at SMA PUSRI Palembang.